Enhancing Educational Practices Through In-Service Training: Elementary School Teacher in Focus - Sampan, Ivy Kate C. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological study explored the experiences of the elementary teachers of Laak South District in their in-service training for professional development. In addition, the researcher wanted to explore the teachers’ experiences on how in-service training applied to improve classroom instruction and impacted on the academic progress of the learners. Qualitative – phenomenological study was employed in exploring the views of the ten (10) elementary teachers of which primary instrument of data gathering was through in- depth interview. Major findings revealed that the experiences of teachers were professional development impact, challenges and opportunities, and collaboration and networking, the tapestry of elementary teachers' experiences in enhancing educational practices through in-service training unfolds, offering insights into the dynamic and evolving nature of education at its core. Likewise, three overarching themes encapsulate the multifaceted hurdles encountered by educators in their pursuit of continuous improvement: resource constraints and time limitations, adapting to educational technology, and addressing diverse learning needs. Lastly, three major themes—efficacy of tailored training approaches, fostering a collaborative professional community, and alignment of training with evolving educational trends—stand as pillars shaping the educational insights derived from this exploration. The research on enhancing educational practices through in-service training for teachers carries significant implications that resonate across educational landscapes. The findings of this study hold the potential to inform and guide educational policymakers, administrators, and institutions in the development and refinement of in-service training programs.